An implementation and outcome evaluation of the Parent Centre's Teen Parenting Programme - Masvosvere, Tulile (Development Policy Research Unit (DPRU), 2024)
Teenage pregnancy and the impact of the HIV epidemic are significant factors leading to adolescents assuming parental responsibilities for children, siblings, or relatives. South African society exhibits diverse family structures and caregiver relationships, extending beyond biological parents to include non-biological caregivers. This study evaluated the Parent Centre's Teen Parenting Programme, a parenting and life skills initiative facilitated by a dedicated team in Nyanga, Gugulethu, and Khayelitsha schools and communities. The programme caters to teenagers with parental responsibilities, encompassing both biological parents and caregivers for younger siblings. Participants voluntarily attended 23 weekly group sessions. The study assessed the programme's implementation, with participants expressing satisfaction with the facilitators' teaching methods and the nurturing atmosphere they fostered. Participants reported positive changes in parenting practices, self-esteem, confidence, and competence, leading to improved parent-child relationships and more effective communication. The study employed a Qualitative Exploratory-Descriptive (QED) research design, guided by a generic qualitative inquiry (GQI) framework to examine practical outcomes and programme implementation. Limitations in causal inference and potential bias due to purposive sampling were acknowledged. Nonetheless, the evaluation provided valuable insights into the strengths of the programme and areas for improvement, contributing to the understanding of teen parenting support programmes.